Reproductive outcome following midtrimester pregnancy loss. (16th November 2010) - Edoo, AWI; Nor, NA Mat; Quinn, C; Fahy, U
Abstract : The aim was to analyse reproductive outcome in pregnancy subsequent to a previous midtrimester pregnancy loss. This was a retrospective case note review over a 4 year period. Patients who had a midtrimester pregnancy loss (>13 and<24 weeks gestation by ultrasound) were identified. A subgroup who achieved subsequent pregnancy formed the study group. The authors assessed their previous pregnancy loss, results of investigations and reviewed their care and outcome in next pregnancy. Of the 86 patients who had midtrimester loss 56 (65%) had a subsequent pregnancy and formed the study group. Median age was 31 and 17 were nulliparous. Median gestation at midtrimester spontaneous abortion was 17 weeks. Pregnancy loss was classified as intrauterine fetal death (22), bleeding (11), fetal abnormality (9), cervical incompetence (6) and prelabour premature rupture of membranes (8). Investigation revealed two maternal thrombophilias, two fetal chromosomal abnormalities, two with two vessel cord and eight with infections. Interventions during the 56 pregnancies included anticoagulation (2), cervical cerclage (6), infection screening (4), detailed ultrasound scanning (8) and cervical length (7). Of the 56 pregnancies, 25% ended in spontaneous abortion; 5.3% had second trimester spontaneous abortions and the preterm delivery rate was 5.4%. Other pregnancy complications included: obstetric cholestasis (1), pre-eclampsia (3), intrauterine growth restriction (1) and threatened preterm labour (1). Take home baby rate was 66% (37). Age <35 was found to be an important prognostic factor (p=0.0003) while parity and number of previous spontaneous abortions were not. At least one quarter of pregnancies ended as spontaneous abortion following a previous midtrimester pregnancy loss. The latter was more likely if the woman was ≥35 years old.